Evaluating the utilisation of ICT as a service delivery tool in urban councils: a case of Harare city council. - Nyahunzvi, Valentine T. (Midlands State University, 2017)
Information and communication technologies (ICTs) are increasingly being incorporated into the internal workings of government, globally. This is done in pursuit of a more effective, efficient and responsive machinery of governance. The research evaluates the utilization of Information Communication and Technology as a service delivery tool in Harare City Council. Research objectives where to establish the link between service delivery and Information Communication and Technology (ICT). Literature review then focused on giving description on the link between ICT and benefits of ICT and challenges been faced by urban councils in developing countries. Mixed methodology was used, stratified random sampling and purposive sampling was used to select the participants. The sample for research was 50 participants which constitute26 employees, 19 residents, 2 ICT managers and 3 councilors. Questionnaires and interviews were employed as research instruments. An overall response rate of 90% was achieved from respondents. Data presentation and analysis was carried out. Finally data wad presented in tables, graphs, pie chart followed by analysis. The findings reveal that the utilisation of ICTs in HCC is not according to acceptable best practices. The research reviewed that internet is accessed via mobile devices in Harare City, the research recommend that HCC must invest in mobile government to improve access to online services. HCC performance with regards to effectiveness in service delivery, the research shows that there is poor ICT literate rate and there is limited access to internet for residents and employees , level of networking connection in departments and households’ access to ICT are very poor. Though there are proven research and imperial evidence to the capacity of ICTs to improve service delivery, there are a number of threats to its adoption and use in HCC. This study identifies some of these impediments like; shortage of skilled ITC personnel, lack of adequate ICT infrastructures, shortage of finance, among others. The paper therefore recommends that government should invest in the provision of ICT infrastructures, as well as in purposeful ICT training.